2000
DOI: 10.1128/jcm.38.10.3853-3855.2000
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Alexon-Trend ProSpecT Campylobacter Microplate Assay

Abstract: We evaluated stool specimens known to contain or be free ofCampylobacter by traditional culture, using the ProSpecTCampylobacter microplate assay (Alexon-Trend, Ramsey, Minn.). This rapid enzyme immunoassay for the detection ofCampylobacter-specific antigens demonstrated 96% sensitivity and 99% specificity and is an acceptable alternative method of Campylobacter detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…These results agree with those obtained by Tolcin et al. [9]. These workers showed no apparent difference between fresh and preserved stool specimens.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results agree with those obtained by Tolcin et al. [9]. These workers showed no apparent difference between fresh and preserved stool specimens.…”
Section: Discussionsupporting
confidence: 93%
“…Since the first evaluation, several studies have shown that the ProSpecT Campylobacter Microplate Assay is sensitive and specific for C. jejuni and C. coli , and that the limit of detection is 3 × 10 6 CFU/mL in fecal specimens [8–10].…”
Section: Introductionmentioning
confidence: 99%
“…Hippurate-positive Campylobacter strains were characterized as Campylobacter jejuni and hippurate-negative isolates as other Campylobacter species. Campylobacter testing directly on fecal samples stored at −70°C was done using a broadly reactive genus-specific ProSpecT enzyme-linked immunosorbent assay (ELISA) [ 33 ]. Details of diagnostic assays for >40 other enteropathogens are described elsewhere [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…Traditional methods for the detection of Shigella and Campylobacter species involve sample culture in selective media followed by a number of biochemical and serological tests. , However, such methods are extremely time-consuming and can take 3−4 days at best to give a result. A number of researchers have explored the use of the polymerase chain reaction (PCR), enzyme-linked immunosorbent assays (ELISA), , or a combination of both for detection of these bacteria and have improved detection time to between 2 h and 2 days, depending on the extent of sample enrichment required. A number of sample matrixes have been analyzed using these techniques, including poultry, environmental water, and stool samples.…”
mentioning
confidence: 99%